Complication Rates after Lateral Plate Fixation of Periprosthetic Distal Femur Fractures: A Multicenter Study. Issue 8 (August 2020) - Campbell, Sean T.; Lim, Philip K.; Kantor, Adam H.; Gausden, Elizabeth B.; Goodnough, L. Henry; Park, Adam Y.; Bishop, Julius A.; Achor, Timothy S.; Scolaro, John A.; Gardner, Michael J.
Highlights: In this series of 55 patients with a periprosthetic distal femur fracture treated with lateral plate fixation, the overall complication rate was 24%. The overall rate of nonunion was 18%, no surgical technique factors were identified as a risk factor for nonunion. Further work is needed to identify strategies to reduce the complication rate in this patient population Abstract: Objective: Periprosthetic fractures of the distal femur can be challenging injuries to treat; nonunion rates of up to 22% have been reported. The purpose of this study was to determine the rate of complications and nonunion in a multicenter series, and to identify patient or surgical factors that were associated with nonunion. Design: Retrospective comparative study Setting: Three Level 1 trauma centers Patients: Fifty-five patients with a periprosthetic distal femur fracture proximal to a total knee arthroplasty. Minimum follow up for inclusion was six months or until union or failure. Intervention: Surgical fixation using a precontoured lateral locking plate Main Outcome Measurement: Fracture union was the primary outcome. Patient demographic and injury variables (age, comorbidities, fracture classification and characteristics) and surgical technique factors (mode of plate fixation, plate material, working length, screw density, and proximal screw type) were identified and compared between patients who developed a nonunion and those who did not. Regression analysis was performed to identify independent risk factors for nonunion. Results: The overall rate of nonunion was 18% and the total complication rate was 24%. After additional surgery, 49 of 55 patients went on to heal (89%). There were no statistical differences in patient demographic or injury variables between the union and nonunion groups, and none of the variables studied were independent risk factors for nonunion in the regression analysis. Conclusions: In this series of 55 patients with periprosthetic distal femur fractures treated with precontoured lateral locking plates, 18% developed nonunion and the overall complication rate was 24%. No patient or surgical variables were identified as risk factors. Future research should seek to identify patients at high risk for complication and nonunion who could benefit from alternative fixation strategies or distal femoral replacement.